Issues of Data Visualization in the Educational Process - G. V.Yeldasheva (Indonesian Journal of Innovation Studies, 2022)
This article discusses about visualization of information provided in the process of learning in the higher education system (lectures, seminars, theoretical materials for practical exercises).